2003
DOI: 10.1128/jb.185.19.5722-5734.2003
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenesσBRegulates Stress Response and Virulence Functions

Abstract: While the stress-responsive alternative sigma factor B has been identified in different species of Bacillus, Listeria, and Staphylococcus, the B regulon has been extensively characterized only in B. subtilis. We combined biocomputing and microarray-based strategies to identify B -dependent genes in the facultative intracellular pathogen Listeria monocytogenes. Hidden Markov model (HMM)-based searches identified 170 candidate B -dependent promoter sequences in the strain EGD-e genome sequence. These data were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
342
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(369 citation statements)
references
References 67 publications
21
342
1
1
Order By: Relevance
“…Recognition of the invasion-defective phenotype of the DsigB strain in non-phagocytic cells (Kim et al, 2004), of P4 inlA as a s B -dependent promoter, and of P2 inlB as a putative s B -dependent promoter (Kazmierczak et al, 2003) identified s B as an important factor contributing to regulation of inlA and inlB. The inlA and inlB genes are transcribed both individually and in an operon (Lingnau et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recognition of the invasion-defective phenotype of the DsigB strain in non-phagocytic cells (Kim et al, 2004), of P4 inlA as a s B -dependent promoter, and of P2 inlB as a putative s B -dependent promoter (Kazmierczak et al, 2003) identified s B as an important factor contributing to regulation of inlA and inlB. The inlA and inlB genes are transcribed both individually and in an operon (Lingnau et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The inlA and inlB genes are transcribed both individually and in an operon (Lingnau et al, 1995). To date, six promoters have been identified in the inlAB locus, which include a confirmed PrfA-regulated promoter (P3 inlA ) and a confirmed s B -dependent promoter (P4 inlA ) upstream of inlA, and a putative s B -dependent promoter (P2 inlB ) upstream of inlB (Kazmierczak et al, 2003;Lingnau et al, 1995). The PrfA-regulated promoter, P3 inlA , is the only promoter reported to generate a bicistronic transcript (Lingnau et al, 1995); therefore, we reasoned that any s B -mediated effects on inlB expression would probably occur through P2 inlB .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several classes of stress-response genes have been described in L. monocytogenes, which are activated during exposure to specific or general stresses. In particular, the class I and class III heat-shock and the SigB response have been investigated thoroughly (Derre et al, 1999;Hanawa et al, 1999;Kazmierczak et al, 2003). Recently, it has been shown that the SOS response of L. monocytogenes is activated upon mild heat exposure (van der Veen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Another four genes encode proteins related to stress. Finally, 30 of the 71 genes are preceded by a sigma B promoter as identified by Kazmierczak et al (2003), suggesting that they might also be regulated in response to stress conditions. Interestingly, more than 50 % of the genes identified by this transcriptomic analysis (49/88 identified) were also found to be regulated during infection of macrophages or Caco-2 cells (Joseph et al, 2006).…”
Section: A Bigot and Othersmentioning
confidence: 99%